Antimicrobial Resistance Profiles of Escherichia coli and Staphylococcus spp. Isolated from Locally Produced Fish and Imported Fish Sold in the Centre Region of Cameroon - Frédéric Moffo; Mohamed Moustapha Fokom Ndebé; Isaac Dah; Esther NNeme Nkolo; Ronald Vougat Ngom; Fabiola Nango Madjeue; Abel Wade; Hélène Tiomo; Victor Ngu Ngwa; Mohamed Moctar Mouliom Mouiche (Journal of Food Protection)
Antimicrobial resistance has emerged as a significant threat to global health, with the World Health Organization (WHO) classifying it among the top 10 public health threats. However, more epidemiological information is needed to support policy and stewardship programs. This study aimed to investigate the antimicrobial resistance profiles of Escherichia coli and Staphylococcus spp. isolated from locally produced and imported fish sold in markets in the Mfoundi Division of the Centre Region of Cameroon. A total of 11 E . coli and 28 Staphylococcus spp. strains were isolated from the 100 fish samples collected in the study area. Antimicrobial susceptibility testing was performed for 16 antimicrobial agents using the disk diffusion method. Overall, multidrug resistance rates of 54.54% (95% confidence interval: 26.9–82.1) and 60.7% (95% confidence interval: 43.7–77.7) were obtained for Escherichia coli and Staphylococcus spp., respectively. The prevalence of antimicrobial-resistant E . coli and Staphylococcus spp. strains was significantly (p < 0.05) higher in locally produced fish (18.6%; 32.6%) than in imported fish (5.3%; 24.6%). According to the WHO Essential Medicines List Access, Watch, and Reserve (AWaRe) classification, the antimicrobial resistance profile of E. coli strains isolates ranged from 5% to 45% for antimicrobials classified as Access and Watch. For Staphylococcus spp., the antimicrobial resistance profile ranges from 7% to 60% for drugs categorized as Access, whereas it ranges from 25% to 100% for drugs belonging to the Watch category. This study revealed that locally produced fish were more contaminated by antimicrobial-resistant E. coli and Staphylococcus spp. than imported fish. The continuous awareness of fish farmers about the appropriate use of aqua drugs is one of the cornerstones for reducing the risk of antimicrobial resistance related to public health.